2017
DOI: 10.14701/ahbps.2017.21.1.52
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of choledochal cyst with pancreas divisum: case presentation and literature review

Abstract: Choledochal cysts are rare congenital malformations of the bile duct characterized by dilatations of the intrahepatic and/or extrahepatic portion of the biliary tree, they are associated to an anomalous arrangement of the pancreaticobiliary duct. Pancreas divisum results from a fusion failure of the pancreatic buds. The coexistence of pancreas divisum and choledochal cyst in adults has been reported in less than 10 well documented cases. This article presents a case of a 42-year-old Peruvian man with intermitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Prior studies suggested that there is about a 30–38% co-existence between the two conditions[21, 22, 23] but a recent larger study suggested the prevalence is as high as 50%[24]. There have reports scattered in the literature with PD co-existing with anomalous pancreatic-biliary junction (APBJ) and choledochal cysts[25, 26, 27, 28, 29]. However, there have been no large-scale studies to support any specific associations between these congenital anomalies.…”
Section: Associated Pancreatic-biliary Anomaliesmentioning
confidence: 99%
“…Prior studies suggested that there is about a 30–38% co-existence between the two conditions[21, 22, 23] but a recent larger study suggested the prevalence is as high as 50%[24]. There have reports scattered in the literature with PD co-existing with anomalous pancreatic-biliary junction (APBJ) and choledochal cysts[25, 26, 27, 28, 29]. However, there have been no large-scale studies to support any specific associations between these congenital anomalies.…”
Section: Associated Pancreatic-biliary Anomaliesmentioning
confidence: 99%
“…Hackert et al have reported a case treated with bile duct resection, papillectomy, hepaticojejunostomy, and jejunal reinsertion of the uncinate pancreatic duct, which is an infrequently performed procedure (15). Other types of CC associated with PD could be managed with preoperative minor papilla sphincterotomy with or without stenting or trans-duodenal papillectomy followed by CC excision (6,9,16,17). In our study, two patients with CC and PD presented with acute pancreatitis.…”
Section: Discussionmentioning
confidence: 60%
“…Although rare, PD can cause intraductal hypertension leading to abdominal pain and recurrent pancreatitis (5). The co-existence of CC and PD and the associated complications are rare, with less than ten documented cases in the literature (6). This report reviews our experience of four cases of CC with PD.…”
Section: Introductionmentioning
confidence: 95%
“…The incidence of choledochal cysts in Asian population is 1 in 1000 live births with predominance in females. In western countries, the incidence ranges from 1:100,000 to 1:150,000 in the United States, 1 in 2 million in the United Kingdom (12). In Uganda, so far this is the second case of giant choledochal cyst in a young female adult that has been managed successful at Mbarara Regional Referral Hospital (13).…”
Section: Follow-up and Outcomesmentioning
confidence: 97%